Public Awareness About Coronary Artery Disease - Mirkhamidova Sevara Mirmakhmudovna; Abdurashitova Sharafat Abdumajidovna; Muyassarova Mukhabbat Mukhammadiyevna; Karimbayev Shakhrambay Dexkanbayevich; Kadeeja Ebrahim Purayan Kottummal (Zien Journals, 2023)
Coronary artery disease is a general term for conditions affecting the heart or blood vessels. It is one of the Major cardiovascular disease affecting the global human population. This disease has been proved to be the major cause of death in both the developed and developing countries. It’s usually associated with a build up of fatty deposits inside the arteries (atherosclerosis)and an increased risk of blood clots and this coronary heart disease occurs when the flow of oxygen rich blood to the heart muscle is blocked or reduced.
Keywords: Cardiovascular disease; Atherosclerosis; Plaque buildup; Cholesterol deposit